P103 A psychosexual needs assessment of patients attending five london sexual health clinics. (8th June 2017) - Malik, Aiysha; Grayer, Justin; Gibson, Stuart
Abstract : Introduction: The aim of this psychosexual needs assessment was to investigate the prevalence and range of sexual problems; to understand the distress, causal attributions and functional impairment associated with these; and to explore patients' service-related needs, in a sample of patients attending sexual health clinics in London. Methods: Questionnaires were disseminated to patients attending five sexual health clinics in London, over a one week period. Nine hundred and thirty four patients responded to the questionnaire. Patients were aged 29.4 years ( SD =8.8) and predominantly female (61.4%). Results: 31.1% of patients indicated they were experiencing a sexual problem. Premature ejaculation, delayed ejaculation, or difficulty having an orgasm were the most prevalent problems reported by patients (13.5%). Female and male patients did not differ in their report of overall sexual problems (32.5% and 28.6%, respectively), however more women reported sexual pain (14.8%, X 2 =11.3, p=.001) and male patients reported difficulties with hypersexuality (9.5%, X 2 =25.2, p<.001). The majority of sexual problems had commenced within the past year, however orgasm, chemsex and hypersexuality problems were longer-standing (>1year). Associated distress was reported by 79.5% of patients. Emotional reasons were attributed as the most likely cause of sexual problems (21.1%). Male patients reported higher functional impairment ( U =1862.0, z=2.3, p =.02). Patients were interested in a range of interventions, and expressed preference to be supported in a sexual health clinic (67.8%). Discussion: The findings present implications for the provision of psychosexual services in sexual health clinics.